Proposed ICDRG Classification of the Clinical Presentation of Contact Allergy. Issue 5 (September 2016) - Pongpairoj, Korbkarn; Ale, Iris; Andersen, Klaus Ejner; Bruze, Magnus; Diepgen, Thomas L.; Elsner, Peter U.; Goh, Chee Leok; Goossens, An; Jerajani, Hemangi; Lachapelle, Jean Marie; Lee, Jun Young; Maibach, Howard I.; et al.
Abstract : The International Contact Dermatitis Research Group proposes a classification for the clinical presentation of contact allergy. The classification is based primarily on the mode of clinical presentation. The categories are direct exposure/contact dermatitis, mimicking or exacerbation of preexisting eczema, multifactorial dermatitis including allergic contact dermatitis, by proxy, mimicking angioedema, airborne contact dermatitis, photo-induced contact dermatitis, systemic contact dermatitis, noneczematous contact dermatitis, contact urticaria, protein contact dermatitis, respiratory/mucosal symptoms, oral contact dermatitis, erythroderma/exfoliative dermatitis, minor forms of presentation, and extracutaneous manifestations.